Sorafenib effectiveness in advanced hepatocellular carcinoma. - Ramos Esquivel, Allan (2018)
Hepatocellular carcinoma (HCC) is the fifth cause of cancer death in Costa Rica for both sexes despite its low incidence. Sorafenib is a tyrosine -kinase inhibitor that is recommended for patients with advanced stage HCC. The purpose of this study is to determine the clinical effectiveness of this drug among Costa Rican patients and to compare it with the available data from scientific literature. A retrospective search was carried out in 40 patients who were candidates for this treatment. Overall survival was calculated according to the Kaplan-Meier method. For patients receiving sorafenib, median overall survival was 12.0 months (Confidence interval 95 %: 7.2 – 16.8 months). The survival rate at one year was 47.7 %. As conclusion, sorafenib confers a positive effect on overall survival as it was reported in medical literature for patients with advanced HCC.